2020
DOI: 10.3390/biology9070169
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Photoautotrophic Growth Regimens of Chlorella sorokiniana in a Photobioreactor for Enhanced Biomass Productivity

Abstract: Microalgae have a wide industrial potential because of their high metabolic diversity and plasticity. Selection of optimal cultivation methods is important to optimize multi-purpose microalgal biotechnologies. In this research, Chlorella sorokiniana AM-02 that was isolated from a freshwater lake was cultured under various high photosynthetic photon flux density (PPFD) conditions and CO2 gas levels in standard Bold’s basal medium (BBM). Furthermore, a wide range of nitrate levels (180–1440 mg L−1) was tested on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…The growth of microalgae and biomass productivity when grown in wastewater or anaerobic digester effluent depend on different factors (such as the features of the culture, physicochemical properties of the wastes, type of a photobioreactor, and technological parameters of the process) [ 28 ]. The microalgal strain Chlorella sorokiniana AM-02 was tested in our previous study [ 27 ], in which we identified the optimal growth conditions in a standard Bold’s Basal Medium (BBM). In this research, a synthetic medium for supplying algae with all the necessary growth compounds was replaced with a diluted anaerobic digester effluent (ADE).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The growth of microalgae and biomass productivity when grown in wastewater or anaerobic digester effluent depend on different factors (such as the features of the culture, physicochemical properties of the wastes, type of a photobioreactor, and technological parameters of the process) [ 28 ]. The microalgal strain Chlorella sorokiniana AM-02 was tested in our previous study [ 27 ], in which we identified the optimal growth conditions in a standard Bold’s Basal Medium (BBM). In this research, a synthetic medium for supplying algae with all the necessary growth compounds was replaced with a diluted anaerobic digester effluent (ADE).…”
Section: Resultsmentioning
confidence: 99%
“…Centrifugation of the digestate contributed to removing particles as well, which gave it a dark color. photons m -2 s -1 [27]. Therefore, we chose 1200 μmol of photons m -2 s -1 in the present study.…”
Section: Growth Of C Sorokiniana Am-02 Under Different Conditionsmentioning
confidence: 99%
See 3 more Smart Citations